2018
DOI: 10.1007/s00232-018-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Artificial Phospholipid Membranes Containing Lauryl Gallate or Cholesterol

Abstract: Lauryl gallate (LG) is an antioxidant agent. However, it exhibits poor solubility in water. Its interactions with the membrane result in structure evolution thus affecting the membrane functionality. In this paper the Brewster angle microscope coupled with the Langmuir trough was applied to determine the morphology, phase behaviour, thickness and miscibility of ternary Langmuir monolayers with equal mole fractions of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC); 1,2-dioleoyl-sn-glycero-3-phosphocholine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The physical and chemical characteristics of the biomimetic materials determine the structure and morphology of the artificial membranes ( Jurak et al, 2018 ). Similarly, the physicochemical properties of the biological membranes are determined by the membrane’s proteins and phospholipids composition.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical characteristics of the biomimetic materials determine the structure and morphology of the artificial membranes ( Jurak et al, 2018 ). Similarly, the physicochemical properties of the biological membranes are determined by the membrane’s proteins and phospholipids composition.…”
Section: Introductionmentioning
confidence: 99%
“… 27 The effect of compression rate, pressure, and time on the shape of domains formed in monolayer at the air–water interface has been studied using a Brewster angle microscope. 28 , 29 A detailed review in the field can be found in ref ( 30 ). All these studies hypothesize that a model membrane with a saturated lipid, cholesterol, and hybrid lipid could be a better system to mimic a biological membrane, as they form nanodomains.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the molecular arrangement of a solution of amphiphilic compounds can be determined by the geometry of the molecules. It can be estimated by the Critical Packing Parameter (CPP) using the following equation: [32][33][34][35][36] CPP…”
Section: Components Of Liposomesmentioning
confidence: 99%
“…If CPP value is <½, formation of spherical micelles will take place, in contrast when >1, formation of inverted micelles will occur. [32][33][34][35][36] Since liposomes are vesicles composed by a lipidic bilayer, CPP of the amphiphilic molecules used for their elaboration should lie between ½ and 1. Phospholipids with two hydrocarbon chains, such as phosphatidic acid, phosphatidylcholine, phosphatidylethanolamine, and phosphatidylglycerol would generate CPP in this range.…”
Section: Components Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation